La metodología científica y la enseñanza de las ciencias : unas relaciones controvertidas - Gil Pérez, D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper we make a review of the relationship between science learning and scientific methodology. We try to show that coherent results of several lines of educative research are contributing to the rising of a science learning model as a conceptual and methodological change, in which students work has the characteristics of research.